Canada : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The Canadian economy bounced back strongly from the effects of the Asian financial crisis and the turmoil in world financial markets last year, reflecting a rebound in commodity prices, continued strong U.S. growth, and strengthening domestic demand, particularly investment spending. Executive Directors commended the authorities for maintaining sound macroeconomic and structural policies over most of the past decade, which had underpinned the strong performance of the Canadian economy, now in its eighth consecutive year of expansion, and welcomed Canada's participation in Financial System Stability Assessments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet